Ajaran Pendidikan Islam Syaikh Syamsuddin As-Sumatrani - Dalmi Iskandar Sultani; Syarifuddin (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2023)
Teachings of Islamic education Shaykh Shamsuddin ibn Abdullah as-Sumatrani. With a literature study approach discussing Shaykh Shamsuddin as-Sumatrani and his teachings in Islamic education as a prominent Muslim intellectual and prominent scholar. As a character who mastered many languages but there was no definite clarity regarding was origins and genealogy of life, it made him interesting to study. Shaykh Syamsuddin as-Sumatrani was born araund 1575-1630 AD, died on 12 Rajab 39H, coinsiding on February 24 1630 AD, died during the war against the Portuguese. Also cnown by the name Syamsuddin Pasai, intellectual, expert scholar of Sufism, fluent in Malay, Javanese, Persian and Arabic. In-depth knowledge of mysticism. Law, history, philosophy, and theology. The title Shaykh al-Islam, the highest title for a scholar, kadi (judge), imam, or sheikh. As advisor to the King, chief priest, member of negotiating team, spokesperson for the Kingdom of Aceh Darusalam. He was a student of Hamzah Fansuri and Fadlullah, who was known from his work entitled Syarh Ruba’i al-Syaih Hamzah Fansuri, Syarah Sya’ir Ikan Tuna. Adhering to the concept of wihdat al-Wujudiyah. Shayh Nuruddin ar-Raniri destroyed ideas that were considered heretical. Althought other researchers considered ar-Raniri’s assessment of Wihdat al-Wujud’s understanding to be wrong, that was, he misunderstood the teachings of Shaykh Hamzah Fansuri and Syamsuddin as-Sumatrani.